Answer with Step-by-step explanation:
We are given that E and F are symmetric matrices of dimension n.
Therefor, E'=E and F'=F
We are given that EF need not be symmetric
If EF may not be commutative then EF necessarily may not be symmetric.
We have to show that E'FE is symmetric .
It means we have to show that (E'FE)'=E'FE
[tex](E'FE)'=(E'(FE))'[/tex]
[tex](E'FE)'=(FE)'(E')'[/tex]
We know that (A')'=A and (AB)'=B'A'
Using the property
[tex](E'FE)'=E'F'E[/tex]
[tex](E'FE)'=E'FE[/tex] (F'=F)
Hence, proved.